PENGARUH FOTOPERIODIK KANIBALISME MATERNAL PADA MENCIT LABORATORIUM (Mus musculus) - Afdhal Tisyan; Rizaldi Rizaldi; Warnety Munir (Scripta Biologica, 2019)
The animal has an ability to respond to environmental changes with an adaptive mechanism to optimize reproductive fitness. Using house mice Mus musculus (laboratory mice) as the subject, we examined the responsiveness to different photoperiod which hints at seasonal change. The animal can accurately predict the seasonal change by physiological anticipation then expressed in their behavior. Cannibalism is one of crucial maternal behavior that helps the population to control its size particularly to survive in significant environmental change. To confirm the significance of photoperiod-induced change in mice maternal cannibalism, which further changed sex ratio and mass regulation,  we placed the mice in different photoperiod: 12h:12h (light:dark; control), 14h:10h (long day), and 10h:14h (short day) as first factor and duration of treatment prior to mating (0 day, 20 days and 40 days) as second factor (n = 5 / group). The results showed that photoperiod has a significant effect (p < 0,05) to the sex ratio of each litter on PND1 (postnatal day 1)  and PND20, while litter size was affected only on PND20. Litter size and sex ratio changes were mainly caused by maternal-specific cannibalism as we observed during 20 days postpartum. PND20 gave significant effect to the pups mass  (p < 0,05). Maternal and pups mass might associate with maternal investment during lactation, and also related to litter size and sex ratio adjustment via specific maternal cannibalism.Key Words: photoperiodism, maternal cannibalism, sex ratio, Mus musculus